2002
DOI: 10.1016/s0014-5793(02)03450-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide increases resistin gene expression in vivo and in vitro

Abstract: Although resistin has been thought to be an important link between obesity and diabetes, recent results do not support this hypothesis. We speculated that resistin may be involved in in£ammatory processes and be induced by in£amma-tory stimuli. In this study, we tested whether lipopolysaccharide (LPS) induced resistin expression in rats. The results show that resistin mRNA levels in white adipose tissue and white blood cells were increased by LPS treatment. LPS also increased resistin mRNA levels in 3T3-L1 adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
2
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 27 publications
(35 reference statements)
5
119
2
6
Order By: Relevance
“…Some pro-inflammatory agents, such as tumor necrosis factor-alpha (Fasshauer et al, 2001), interleukin-6 (Kaser et al, 2003) and lipopolysaccharide (Lu et al, 2002), can regulate resistin gene expression. Other studies have also shown the regulation of pro-inflammatory cytokine expression by resistin (Bokarewa et al, 2005;Silswal et al, 2005;Pang and Le, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some pro-inflammatory agents, such as tumor necrosis factor-alpha (Fasshauer et al, 2001), interleukin-6 (Kaser et al, 2003) and lipopolysaccharide (Lu et al, 2002), can regulate resistin gene expression. Other studies have also shown the regulation of pro-inflammatory cytokine expression by resistin (Bokarewa et al, 2005;Silswal et al, 2005;Pang and Le, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Placental leptin mRNA production is up-regulated by TNF-and IL-6 (Chardonnens et al 1999, Soh et al 2000, Cameo et al 2003, Nuamah et al 2004, and although there is little information available on the regulation of resistin and adiponectin within intrauterine tissues, resistin expression is up-regulated by LPS and suppressed by TNF- (Lu et al 2002, Shojima et al 2002, Kaser et al 2003, and adiponectin gene expression and secretion is inhibited by TNF- (Kappes & Loffler 2000, Halleux et al 2001) and IL-6 . In this study, there was no effect of LPS or proinflammatory cytokines on the release of leptin, resistin and adiponectin from gestational and maternal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to mice, only a low level of expression of resistin has been found in mature adipocytes in humans [24][25][26][27]. In humans, resistin is highly expressed in the bone marrow compared to other tissues [28], but it is also present in trophoblastic cells of placenta, pancreas, primary cell leukemia, synovial fluid, synovial tissue, and circulating blood [22,24,[28][29][30][31][32][33][34]. The particular cells that express resistin in white adipose tissue are monocytes and macrophages [26,28,35].…”
Section: Sites Of Resistin Productionmentioning
confidence: 99%